2016
DOI: 10.2147/ott.s104556
|View full text |Cite
|
Sign up to set email alerts
|

Metadherin regulates epithelial–mesenchymal transition in carcinoma

Abstract: Metadherin (MTDH) was first identified in primary human fetal astrocytes exposed to HIV-1 in 2002 and then recognized as an important oncogene mediating tumorigenesis, progression, invasiveness, and metastasis of carcinomas. Epithelial–mesenchymal transition (EMT) is a vital process in embryonic development, organ repair, and cancer progression. MTDH and EMT have also been proved to be related to the prognosis of patients with cancers. Recent studies reveal a relationship between MTDH overexpression and EMT in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…Negative correlations between AEG‐1 and E‐cadherin, or positive correlations between AEG‐1 and vimentin, have been identified in hepatocellular carcinoma 44, lung cancer 45, laryngeal squamous cell carcinoma 46, squamous cell carcinoma of the head and neck 47 and osteosarcoma 48. Other studies have confirmed that overexpression or downregulation of AEG‐1 expression regulates EMT, migration or invasion in vitro in liver cancer cells 43, head and neck squamous cells 47, cervical cancer cells 49, and lung cancer cells 35, and in animal breast cancer models 50. However, similar studies on gastric cancer are lacking.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Negative correlations between AEG‐1 and E‐cadherin, or positive correlations between AEG‐1 and vimentin, have been identified in hepatocellular carcinoma 44, lung cancer 45, laryngeal squamous cell carcinoma 46, squamous cell carcinoma of the head and neck 47 and osteosarcoma 48. Other studies have confirmed that overexpression or downregulation of AEG‐1 expression regulates EMT, migration or invasion in vitro in liver cancer cells 43, head and neck squamous cells 47, cervical cancer cells 49, and lung cancer cells 35, and in animal breast cancer models 50. However, similar studies on gastric cancer are lacking.…”
Section: Discussionmentioning
confidence: 93%
“…The promotion of metastasis by AEG-1-induced EMT has been demonstrated in a variety of malignancies. Combined detection of AEG-1 and EMT biomarkers in the same species of human tissues, and comparisons of their expression in metastatic tissues with non-metastatic tissues, has been done on patient samples to reveal their relationship [43]. Negative correlations between AEG-1 and E-cadherin, or positive correlations between AEG-1 and vimentin, have been identified in hepatocellular carcinoma [44], lung cancer [45], laryngeal squamous cell carcinoma [46], squamous cell carcinoma of the head and neck [47] and osteosarcoma [48].…”
Section: Discussionmentioning
confidence: 99%
“…MTDH, a known regulator of EMT (37), was significantly higher expressed in the fast-growing tumors, and the wound-healing assay demonstrated MTDH to be a contributor in cell migration, an important characteristic of mesenchymal cells. Moreover, silencing of MTDH led to a more epithelial and less aggressive profile, reassuring its role.…”
Section: Discussionmentioning
confidence: 97%
“…The epithelial–mesenchymal transition (EMT) is a complex and multi‐step biological process that serves as a key role in modulating tumor cell metastasis . SNHG20 has been showed to be involved in EMT process .…”
Section: Discussionmentioning
confidence: 99%